2019
DOI: 10.1002/jclp.22751
|View full text |Cite
|
Sign up to set email alerts
|

Rumination moderates the role of meaning in the development of prolonged grief symptomatology

Abstract: Objective:: To address the etiology of prolonged grief disorder (PGD) by examining whether rumination moderates the role of meaning-making in mediating the impact of PGD risk factors. Method:: A survey assessing PGD risk factors (low social support, insecure attachment, violent loss, neuroticism, and loss of a spouse), meaning, and rumination was administered 2-12 months postloss among adults across North America and Europe (mean age = 44.3, 71.9% female). At a 7-10 months follow-up, symptoms of PGD were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
0
21
0
2
Order By: Relevance
“…However, as unfinished business–related distress was similarly associated with prolonged grief, 15 an alternative explanation is that parents’ focus on regrets and/or unfinished business hinders the processing of grief and adaptation, 45 maintaining prolonged grief symptoms over time. Both prolonged grief 46,47 and regret 11 have been linked to ruminative thinking, which is more common in women. 48 This may be in part why a greater proportion of mothers than fathers reported regrets and unfinished business.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as unfinished business–related distress was similarly associated with prolonged grief, 15 an alternative explanation is that parents’ focus on regrets and/or unfinished business hinders the processing of grief and adaptation, 45 maintaining prolonged grief symptoms over time. Both prolonged grief 46,47 and regret 11 have been linked to ruminative thinking, which is more common in women. 48 This may be in part why a greater proportion of mothers than fathers reported regrets and unfinished business.…”
Section: Discussionmentioning
confidence: 99%
“…68 Regrets can also be alleviated through behavioral approaches, including completing something that was left incomplete. 11 As ruminative preoccupation has been found to exacerbate struggles to find meaning in the loss, which in turn prospectively predicts greater prolonged grief symptoms, 46 interventions that use imaginal work (e.g. letters, empty chair dialogues) and that focus on meaning reconstruction of events related to regrets, 69 such as Meaning-Centered Grief Therapy (MCGT), 70,71 may also have benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Bellet, Neimeyer, and Berman (2018) found a moderating, buffering role of meaning made on the prediction of protracted grief by the centrality of the loss in the life of the respondents. Milman and colleagues (2019) found a mediating role of meaning made for predicting protracted grief by a series of risk factors, which in turn was moderated by ruminative tendencies; thus, the stronger the ruminative tendency, the weaker the prediction of protracted grief by meaning made. Finally, Hasson‐Ohayon, Peri, Rotschild, and Tuval‐Mashiach (2017) found that self‐reported integration of the event into self‐narrative (a proxy to meaning made) mediated the relation between dissociative tendencies and protracted grief.…”
Section: Meaning Making‐attempts Meaning Made and Adjustmentmentioning
confidence: 99%
“…This finding could be due to grievers’ attempts to cope with intense grief by searching for meaning or participating in spiritual practices. It is possible that some individuals striving to find meaning may engage in rumination; however, ruminative meaning making may worsen symptoms of prolonged grief, as individuals can become stuck in a struggle to find meaning from their loss (Milman et al., 2019).…”
Section: Discussionmentioning
confidence: 99%